Why would the users of Google's cloud services intend to switch to alternative services? - Chulmin Lim; Seongcheol Kim (International Telecommunications Society (ITS), 2022)
As the amount of data collected by individuals increases and working and education environments are digitalized, the demand for personal cloud storage services (PCSS) has been expanded as well. Users can upload their data to the storage in the cloud service and use or share the data seamlessly through multiple devices. Global service providers such as Google and Microsoft have led this market based on their high cloud computing technology and extensive user network, providing free basic service to all users. Google, however, has changed its Google Photos from free to paid service according to the new cloud service policy. Considering diverse opinions and evaluations on the change, this study aims to analyze the users' response to Google's PCSS and service charging policy. This study examines the factors affecting cloud service users' intention to switch to alternative services based on the push-pullmooring (PPM) framework in the context of South Korea. The result of this study provides some practical and policy implications for cloud service providers, IT-related institutions, and government.
Keywords: 330; Google cloud service; Personal cloud storage service (PCCS); Switching intention; Push-Pull-Mooring (PPM) framework